THE ACCEPTABILITY OF TECHNOLOGY FOR FOREIGN LANGUAGE TEACHING - Usmanova K. Kh. (Bright Mind Publishing, 2025)
The provided article explores the effectiveness of modern technology in teaching English as a foreign language (EFL). It argues that technology, encompassing not just devices but also innovative methods and systems, is crucial for improving the language learning process. The use of tools like computers, multimedia, mobile applications, and the internet provides students and teachers with vast resources, making learning more comprehensive and engaging. Technology helps learners acquire and improve language skills by consolidating various components of the learning system, thereby helping to achieve desired educational outcomes. The internet, in particular, offers immediate, unlimited access to software and platforms that can accelerate English teaching and learning. The article also notes that the teacher's role is essential in effectively integrating these tools and that many applications are specifically designed to boost both teaching effectiveness and student understanding. The article is the significant difference in learning environments and motivation between EFL students in Uzbekistan and ESL students in the United States. Uzbek students have minimal exposure to English outside the classroom and often learn through outdated methods, which can lead to low internal motivation. For them, technology like TV and the internet serves as a primary source of authentic language materials. A comparative study mentioned in the text found a major difference in motivation levels between Uzbek EFL learners and US ESL learners, concluding that technology integration can significantly boost student motivation. Furthermore, the article highlights that while research on technology's effectiveness in language education has been limited in scope—often focusing on higher education and specific language skills—the existing studies consistently show a pattern of positive effects.
Keywords: Technology, multimedia, a comparative study, technology integration, innovative methods, foreign languages.